Economic diagnostics of the efficiency of digital platform utilization in the interaction of construction development enterprises - Khomenko, O. (Ways to Improve Construction Efficiency, 2022)
The article reveals the conceptual and applied aspects of forming digital platforms in the field of construction development as an important factor of economic integration of enterprises and ensuring their competitiveness under conditions of digital economic transformation. It is substantiated that digital platforms represent not only a technological environment but also a new type of economic structure capable of reshaping market actor interactions, generating new sources of added value, and creating network synergy effects. The functional purpose of digital platforms is analyzed as a foundation for building modern business ecosystems, within which disparate development, design, construction and installation, financial, and operational processes are integrated. It is demonstrated that such platforms contribute to reducing transaction costs, increasing the transparency of contractual relations, accelerating project management processes, optimizing logistics, and supporting decision-making based on big data and business analytics. Key types of platforms in development are identified: coordination, infrastructure, contractual, analytical, marketplace, and specialized technological platforms (e.g., BIM environments). A system of ten analytical models for economic diagnostics of business ecosystem development based on digital platforms is proposed. These models include: the platform lifecycle model, synergy model, value platform model, digital maturity model, functional alignment model, institutional compatibility model, innovation impulse model, transactional efficiency model, knowledge dynamics model, and interaction intellectualization model. For each model, the analytical purpose, evaluation indicators, and practical use cases are defined. The need to update the toolkit of economic and managerial diagnostics of construction enterprises, considering their integration into digital ecosystems, is emphasized. The proposed approach is focused on a strategic vision of digital transformation, which is based on the integration of managerial, financial-economic, technological, and cultural factors. The results obtained have practical value for developing digital development policies in the construction sector and enhancing the investment attractiveness of development projects.